LO35: Impact of EMS direct referral to community care on services received. (15th May 2017) - Van Aarsen, K.; CHE, A. Dukelow; Lewell, M.; Loosley, J.R.; Pancino, S.
Abstract : Introduction: The Community Referral by Emergency Medical Services (CREMS) program was implemented in January 2015 in Southwestern Ontario. The program allows Paramedics, who are interacting with a patient as a direct result of a call to 9-1-1, to directly refer patients in need of home care support to their local Community Care Access Centre (CCAC) for needs assessment. If indicated, subsequent referrals are made to specific services (e.g. nursing, physiotherapy and geriatrics) by the CCAC. Ideally, CREMS connects each patient with appropriate, timely care, supporting individual needs. Similar referral programs have been implemented in communities with preliminary data showing positive results. The primary objective of this project was to evaluate the success of the CREMS program by determining the number of referrals made by EMS in London-Middlesex to CCAC since implementation as well as the proportion of referred patients receiving a new or increase in service due to EMS referral.Methods: Data for all CCAC referrals from London-Middlesex EMS was collected for a thirteen month period (February 2015-February 2016). Data was evaluated for quantity of referrals and proportion that led to a patient receiving new or increased home care service.Results: There were 436 referrals made in the study period which represented 391 individuals. 54% of patients were between 65-84 years of age. Of the 391 patients, 162 (41%) were not known to CCAC and of those 119 (73%) received a new service due to EMS referral. The most common new services were occupational therapy (61%) and nursing (47%). Of the 229 (59%) of patients that were already known to CCAC, 101 (44%) received an increase in service due to EMS referral. No patients refused a new or increase in service.Conclusion: Of all patients referred to CCAC, 56% received a new service or had a change in existing services which suggests that a large number of patients benefited from early EMS referral to community services. The results of this project provide impetus to continue and expand the CREMS program. Future studies will evaluate if the implementation of this program has reduced patient reliance on 911 requests for paramedic care as well as Emergency Department transports.